Design of a Prototype of Water Purification by Plasma Technology as the Foundation for an Industrial Wastewater Plant. - Barillas-Mora, Laura (2015)
https://www.scopus.com/inward/record.url?eid=2-s2.0-84938099563&partnerID=40&md5=c53190f5ec3d59b3c1bee87e74b2f904